A computational study on the SO2 adsorption by the pristine, Al, and Si doped BN nanosheets. (December 2016) - Behmagham, F.; Vessally, E.; Massoumi, B.; Hosseinian, A.; Edjlali, L.
Abstract: It has been previously indicated that SO2 gas cannot be detected by graphene and a carbon nanotubes. Herein, the reactivity and electronic sensitivity of a boron nitride (BN) nanosheet and its Al- and Si-doped forms to the SO2 gas was investigated, using density functional theory. It was mainly found that, 1) the BN sheet has a good sensitivity to SO2 gas, but it suffers from a weak interaction energy, 2) replacing a B atom of the BN sheet by an Si atom significantly increases its reactivity but does not change the sensitivity, 3) the Al-doping moderately increases the reactivity and significantly improves the sensitivity. The adsorption energy is about −7.3, −24.3, and −51.3 kcal/mol on the pristine, Al-doped and Si-doped BN sheets. After the adsorption of SO2 gas on the Al-doped BN sheet, it is converted from a semiconductor to a semimetal compound, indicating that it may be used in the SO2 sensor devices. A recovery time of about 23.8 min at 298 K and 27.6 s at 335 K is predicted for Al-doped BN sheet. Also, the effect of density functional on the results are investigated. Highlights: BN sheet shows a good sensitivity to SO2 gas, but suffers from a weak interaction. Al-doping increases the reactivity and significantly improves the sensitivity. Al-doped BN nanosheet may be used in the SO2 sensor devices. A recovery time of about 27.6 s is predicted for Al-doped BN sheet at 335 K.